A Qualitative Exploration of Essential Content for Peace Education Curricula to Prevent Digital Violence - Deodatus Kolek; Rusman Rusman (Sekolah Tinggi Agama Islam Kuningan, 2026)
Background: Digital violence, including cyberbullying, hate speech, doxing, and online gender-based violence, has surged in Indonesian schools, with over 445,000 cases reported in 2024. Despite its growing prevalence, limited systematic analysis has been conducted to identify which curricular components of peace education can effectively address digital violence in Indonesia’s multicultural school contexts. Objective: This study aims to identify and synthesise key curricular components of peace education to prevent digital violence in Indonesian multicultural schools, integrating Tyler’s four-stage curriculum rationale, UN human dignity principles, Indonesian local cultural values (gotong royong, musyawarah), and digital ethics into the proposed PEACE-D Framework. Method: A Systematic Qualitative Review (SQR) was conducted, synthesising 45 peer-reviewed articles (2017–2026) retrieved from Scopus, Google Scholar, and Garuda Portal. The data was analysed using Braun & Clarke’s six-phase thematic analysis, validated by investigator triangulation, achieving 87% intercoder agreement. Result: Thematic synthesis identified four core curricular domains forming the PEACE-D Framework: (1) cross-national peace competencies (knowledge, attitudes, and skills for conflict transformation); (2) human personal dignity (UN-grounded digital privacy and non-degradation norms); (3) contextual cultural values (gotong royong, musyawarah, Sufistic empathy as cyber-ethical foundations); and (4) digital ethics and online responsibility (netiquette, cyberbullying prevention, bystander intervention). Conclusion: The PEACE-D Framework advances curriculum theory by integrating Tyler’s rationale with cultural and ethical dimensions specific to Indonesia’s digital educational context. Practical implications include adaptive module development within Kurikulum Merdeka and policy integration at the national level. Future quasi-experimental research in multicultural schools is recommended to empirically validate framework effectiveness.